"Willingness to Pay": The Value Attributed to Program Location by Pulmonary Rehabilitation Participants. (1st July 2021) - Burge, Angela T.; Holland, Anne E.; McDonald, Christine F.; Hill, Catherine J.; Lee, Annemarie L.; Cox, Narelle S.; Moore, Rosemary; Nicolson, Caroline; O'Halloran, Paul; Lahhama, Aroub; Gillies, Rebecca; Mahal, Ajay
Abstract: The "contingent valuation" method is used to quantify the value of services not available in traditional markets, by assessing the monetary value an individual ascribes to the benefit provided by an intervention. The aim of this study was to determine preferences for home or center-based pulmonary rehabilitation for participants with chronic obstructive pulmonary disease (COPD) using the "willingness to pay" (WTP) approach, the most widely used technique to elicit strengths of individual preferences. This is a secondary analysis of a randomized controlled equivalence trial comparing center-based and home-based pulmonary rehabilitation. At their final session, participants were asked to nominate the maximum that they would be willing to pay to undertake home-based pulmonary rehabilitation in preference to a center-based program. Regression analyses were used to investigate relationships between participant features and WTP values. Data were available for 141/163 eligible study participants (mean age 69 [SD 10] years, n = 82 female). In order to undertake home-based pulmonary rehabilitation in preference to a conventional center-based program, participants were willing to pay was mean AUD176 (SD 255) (median 83 [IQR 0 to 244]). No significant difference for WTP values was observed between groups ( p = 0.98). A WTP value above zero was related to home ownership (odds ratio [OR] 2.95, p = 0.02) and worse baseline SF-36 physical component score (OR 0.94, p = 0.02). This preliminary evidence for WTP in the context of pulmonary rehabilitation indicated the need for further exploration of preferences for treatment location in people with COPD to inform new models of service delivery.